Shockvertising - Viewers’ visual communication perspectives of a controversial skincare advertisement - Rahman, Amir Lukman Abd; Mohamad, Hairul Azhar; Wahab, Nadiah Hanim Abdul; Rashid, Muhammad Haziq Abd (Faculty of Social and Political Science, Universitas Airlangga, 2024)
The rise of digital advertising has led to the creation of various innovative materials to capture the target market’s attention. To stay competitive, many advertisers use “shockvertising”, creating controversial advertisements with a significant impact on viewers’ attitudes and sentiments. This survey research is based on Lester’s Six Perspectives in Visual Communication theory which explained that viewers’ personal, historical, technical, cultural, ethical and critical perspectives are the determining factor in nalysing their controversial consideration perception. In this study, the use of the theory is to explore viewers’ perspectives on a controversial Malaysian skincare advertisement. Using a quantitative approach, 250 respondents rated their perception of a SlimmeWhite skincare TV advertisement. The responses were analysed using SPSS to address three research questions, finding correlations and mean results. The study found that personal technical and ethical perspectives significantly influenced viewers’ attitudes towards the advertisement, identifying these as the controversial aspects. In contrast, critical and cultural perspectives were the least controversial. The advertisement was deemed highly controversial, but gender did not affect viewers’ perspectives. This research concludes that the resulting data are very valuable for advertising students, brand advertisers and companies in understanding viewers’ perspectives on controversial elements in Malaysian skincare advertisements.